Amino lithium salt, polymer electrolyte and preparation method thereof
The polymer electrolyte is prepared by synthesizing a new lithium amino salt and reacting with polymer, which solves the problem of fire and insufficient energy density in liquid electrolytes in lithium-ion batteries, and achieves high lithium ion migration number and increased energy density.
Patent Information
- Application Number
- CN202411816257.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-25
AI Technical Summary
The liquid electrolytes in existing lithium-ion batteries are prone to fire or explosion during use, and the energy density is close to the structural limit, which cannot meet the needs of high energy density.
A new type of lithium amino salt is synthesized by molecular design and reacted with polymer to prepare polymer electrolyte. The main chain is polyester, which can form a coordination effect with lithium ions and improve the migration efficiency of lithium ions.
The number of lithium ion migrations is close to 1, which reduces the ion concentration gradient inside the battery and improves the power density and energy density of the lithium ion battery.
Smart Images

Figure CN119874571A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium metal battery polymer electrolytes, and in particular to an amide lithium salt and a polymer electrolyte and a preparation method thereof. Background Art
[0002] As a highly efficient energy storage device, lithium-ion batteries have been widely used in the field of consumer electronics and electric vehicles. They have the advantages of high specific energy, low self-discharge, high operating voltage, high power density, and no memory effect. The current liquid electrolyte will react with the electrodes during the use of the battery, causing the battery performance to decline, and it is easy to cause fire or even explosion when subjected to external impact, squeezing and stimulation. In addition, the energy density of liquid electrolyte batteries has approached the structural limit and cannot meet the current demand for high energy density in power batteries. With the continuous improvement of the requirements for battery safety and energy density, solid-state batteries have received widespread attention and research, and solid-state electrolytes have become a research hotspot. Polymer solid electrolytes have the advantages of good processing performance, adjustable mechanical properties, and good contact with the electrode interface. They are one of the potential candidate materials for solid-state battery electrolytes.
[0003] Unlike lithium salts used in traditional liquid electrolytes, imide lithium salts used in polymer solid electrolytes usually have larger anions, high ionic conductivity, high electrochemical stability, better thermal stability and chemical stability. The molecular structure of imide lithium salts can be adjusted by chemical modification to optimize their performance. By introducing different functional groups in the molecular structure, its solubility, conductivity and stability can be adjusted to meet the needs of different types of polymer electrolytes. The molecular structure of imide lithium salts can be adjusted by chemical modification to optimize their performance. By introducing different functional groups in the molecular structure, its solubility, conductivity and stability can be adjusted to meet the needs of different types of polymer electrolytes.
[0004] The basic components of solid polymer electrolytes include polymer matrix and lithium salt. The polymer matrix is polyethylene oxide (PEO), etc. There is an anion concentration gradient during the cycle under high-density current, which leads to dendrite growth and limited charging rate. In order to achieve single-ion conduction, lithium salt is embedded in the polymer matrix. The single-ion conductor fixed on the polymer chain by chemical bonding or physical entanglement, lithium ions conduct electricity through the coordinated movement with the polymer chain segments, while the anions are fixed, and the migration number of lithium ions is close to 1, which significantly improves the ion conduction efficiency and avoids the negative impact of anion migration on battery performance.
[0005] The strong binding between anions and lithium ions in single-ion conductors hinders the rapid transmission of lithium ions, resulting in low ionic conductivity, which hinders the practical application of single-ion conductors. Most of the current single-ion conductors are prepared by free radical polymerization, and their main chain structure is a carbon chain, without groups that coordinate with lithium ions, so the main chain structure does not contribute to the migration of lithium ions. The molecular structure of imide lithium salts can be adjusted. The present invention synthesizes a new type of amino lithium salt through molecular design, and prepares a polymer electrolyte by reacting with a polymer. Its main chain is polyester, which can form a coordination effect with lithium ions, which is beneficial to the migration of lithium ions and improves the utilization efficiency of the polymer. Compared with the lithium salt designed by patent CN 112952191 A, lithium salts with amino groups can perform more reactions, and because the amino group is more active, the reaction conditions are milder, so more electrolyte structures can be prepared. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an amino lithium salt and a polymer electrolyte and a preparation method thereof. The lithium salt with an amino group has higher activity and can react with a polymer matrix to prepare a single ion conductor solid polymer electrolyte with a high lithium ion migration number.
[0007] In order to achieve the above object, the technical solution of the present invention is: an amide lithium salt, the structural formula of the amide lithium salt is shown in formula (I),
[0008]
[0009] In the formula, R 1 and R 2 Each is independently selected from a substituted or unsubstituted alkyl, a substituted or unsubstituted alkenyl, a substituted or unsubstituted alkynyl and a substituted or unsubstituted heteroatom-containing group; wherein, when substituted, the substituent is selected from halogen; the heteroatom includes at least one of B, N, O, Si, P, and S, the number of carbon atoms in the alkyl is less than or equal to 10, the number of carbon atoms in the alkenyl is less than or equal to 10, and the number of carbon atoms in the alkynyl is less than or equal to 10.
[0010] Further; prepared by reacting sulfonamide hydrochloride and sulfonyl chloride, the structural formula of the sulfonamide hydrochloride is shown in formula (II), and the structural formula of the sulfonyl chloride is shown in formula (III);
[0011]
[0012] The molar ratio of the sulfonamide hydrochloride to the sulfonyl chloride is 1:1.
[0013] Another technical solution of the present invention is: a method for preparing the lithium amide salt, comprising the following steps:
[0014] (1) Amino group protection of amino hydrochloride: sulfonamide hydrochloride and di-tert-butyl dicarbonate were stirred in an alkaline solvent for reaction. The resulting reaction solution was diluted with dichloromethane and then treated with 1 mol / L HCl aqueous solution and saturated NaHCO 3 After washing, the organic phase is dried and concentrated by rotary evaporation to obtain the N-tert-butyloxycarbonylamino compound;
[0015] (2) Synthesis of lithium amide salt precursor: Under argon atmosphere, the N-tert-butyloxycarbonylamino compound prepared in step (1) and sulfonyl chloride are reacted in an organic solvent at a molar ratio of 1:(1-1.5), the obtained reaction solution is concentrated by rotary evaporation, dichloromethane is added to dissolve, and then NaHCO 3 The solution is washed with an aqueous solution of HCl, the organic phase is dried and then the solvent is removed by rotary evaporation to obtain N-tert-butyloxycarbonylsulfonyl imide;
[0016] (3) Removal of the protecting group of lithium amide salt: the N-tert-butyloxycarbonylsulfonyl imide prepared in step (2) is reacted in trifluoroacetic acid or an acid solution of HCl aqueous solution / organic solvent, and stirred. The obtained reaction solution is then evaporated to remove the solvent to obtain aminosulfonyl imide hydrochloride;
[0017] (4) Neutralization reaction of amide lithium salt: neutralize the aminosulfonyl imide hydrochloride prepared in step (3) with lithium hydroxide in a solvent to obtain amide lithium salt.
[0018] Further, step (1) is: dissolving sulfonamide hydrochloride and di-tert-butyl dicarbonate in tetrahydrofuran, adding 2 equal parts of sulfonamide hydrochloride to N,N-diisopropylethylamine or triethylamine, stirring and reacting for 48 hours, diluting the obtained reaction solution with dichloromethane, and then successively using 1 mol / L HCl and saturated NaHCO 3 The organic phase is washed, dried and concentrated by rotary evaporation to obtain the N-tert-butyloxycarbonylamino compound; the molar ratio of the sulfonamide hydrochloride to di-tert-butyl dicarbonate is 1:(1-1.5).
[0019] Further, step (2) is: under an argon environment, the N-tert-butoxycarbonylamino compound prepared in step (1) is mixed with 4-dimethylaminopyridine (DMAP) and triethylamine and dissolved in acetonitrile to obtain an N-tert-butoxycarbonylamino compound solution, sulfonyl chloride is dissolved in acetonitrile to obtain a sulfonyl chloride solution, the sulfonyl chloride solution is added to the N-tert-butoxycarbonylamino compound solution, the reaction is first carried out at 0°C for 30 minutes, and then stirred at room temperature for 48 hours, the obtained reaction solution is concentrated by rotary evaporation, dichloromethane is added to dissolve, and then 3wt% to 5wt% NaHCO is used in sequence. 3 and washing with 1 mol / L HCl, drying the organic phase and then removing the solvent by rotary evaporation to obtain N-tert-butyloxycarbonylsulfonyl imide;
[0020] The molar ratio of the N-tert-butoxycarbonylamino compound, 4-dimethylaminopyridine, triethylamine and sulfonyl chloride is 1:1:3:(1-1.5); the concentration of the N-tert-butoxycarbonylamino compound in the N-tert-butoxycarbonylamino compound solution is 0.5 mol / L, and the concentration of the sulfonyl chloride solution is 0.5 mol / L.
[0021] Furthermore, step (3) is: the N-tert-butoxycarbonylsulfonyl imide prepared in step (2) is stirred in trifluoroacetic acid or 1-2 mol / L HCl aqueous solution / tetrahydrofuran acid solution for reaction for 48 hours, and the obtained reaction solution is subjected to rotary evaporation to remove the solvent to obtain aminosulfonyl imide hydrochloride, wherein the volume ratio of the HCl aqueous solution to tetrahydrofuran is 1:1, the molar ratio of the N-tert-butoxycarbonylsulfonyl imide to trifluoroacetic acid is 1:2, and the molar ratio of the N-tert-butoxycarbonylsulfonyl imide to HCl in the acid solution is 1:2.
[0022] Furthermore, in step (4), the molar ratio of aminosulfonyl imide hydrochloride to lithium hydroxide is 1:2, and the solvent is selected from any one of water, N,N-dimethylformamide, and dimethyl sulfoxide.
[0023] Another technical solution of the present invention is: a polymer electrolyte, prepared by reacting the amino lithium salt described in claim 1 with a polymer matrix, wherein the polymer matrix has a structural formula as shown in formula (IV),
[0024]
[0025] In the formula, R 3 One selected from hydrogen, halogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted heteroatom-containing group, wherein, when substituted, the substituent is selected from halogen; the heteroatom includes at least one of B, N, O, Si, P, S, the number of carbon atoms in the alkyl is less than or equal to 10, the number of carbon atoms in the alkenyl is less than or equal to 10, and the number of carbon atoms in the alkynyl is less than or equal to 10;
[0026] The preparation method is as follows: reacting the structural units of the amino lithium salt and the polymer matrix in an alkaline solvent at a molar ratio of 1:1 for 3 hours with stirring, and removing the solvent after rotary evaporation or dialyzing the obtained reaction solution in pure water to obtain a polymer electrolyte with a structural formula as shown in formula (V). The alkaline solvent is N,N-dimethylformamide or dimethyl sulfoxide containing 1% triethylamine.
[0027]
[0028] Another technical solution of the present invention is: a polymer electrolyte, the preparation method is: reacting the amino lithium salt described in claim 1 with a dibasic acid, a dialdehyde, and an isonitrile in a molar ratio of 1:0.5:0.5:1 to obtain a polymer electrolyte, the structural formula of which is shown in formula (VI),
[0029]
[0030] Formula (VI)
[0031] In the formula, R 4 -R 6 One selected from substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aromatic group, substituted or unsubstituted heteroatom-containing group, wherein, when substituted, the substituent is selected from halogen; the heteroatom includes at least one of B, N, O, Si, P, S, the number of carbon atoms in the alkyl is less than or equal to 10, the number of carbon atoms in the alkenyl is less than or equal to 10, and the number of carbon atoms in the alkynyl is less than or equal to 10.
[0032] Further; the polymer electrolyte also includes other components, and the other components are selected from lithium perchlorate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium oxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, bis(difluorosulfonyl)imide lithium salt, bis(trifluoromethylsulfonyl)imide lithium, ether, benzene, toluene, xylene, chloroform, carbon disulfide, acetonitrile, acetone, N,N-dimethylpyrrolidone, N,N-dimethylformamide, ethylene carbonate, propylene carbonate, butylene carbonate, ethylene sulfite, propylene sulfite, dimethyl sulfite, diethyl sulfite, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, One or more of allyl methyl carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, ethyl propionate, propyl propionate, ethyl acetate, ethyl butyrate, γ-butyrolactone, ethylene glycol dimethyl ether, tetrahydrofuran, tetrahydropyran, dioxolane, dimethyl sulfoxide, dimethyl sulfone, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid, polyacrylonitrile, polymethyl methacrylate carbonate, polyethylene oxide, polyethylene, polypropylene, polyamide, polyimide, polyvinyl alcohol, polyvinyl butyral, polysiloxane, polytetrafluoroethylene, polytrimethylene carbonate, inorganic filler oxide solid electrolyte, sulfide solid electrolyte, silicon oxide, silicon dioxide, titanium oxide, zirconium oxide, aluminum oxide, boehmite, montmorillonite, and succinonitrile.
[0033] Beneficial effects of the present invention: The present invention synthesizes a new type of amino lithium salt through molecular design, and prepares a polymer electrolyte by reacting with a polymer. The main chain of the polymer is polyester, which can form a coordination effect with lithium ions, which is beneficial to the migration of lithium ions and improves the utilization efficiency of the polymer. Compared with the lithium salts designed by the prior art, lithium salts with amino groups can perform more reactions, and because the amino group is more active, the reaction conditions are milder, so more electrolyte structures can be prepared. The unique advantage of the amino lithium salt synthesized by the present invention and its single-ion conductor solid polymer electrolyte is that its lithium ion migration number is close to 1. When used as an electrolyte, it can effectively reduce the ion concentration gradient inside the battery and improve the efficiency of lithium ion migration, which is of great significance for improving the power density and energy density of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The H-NMR spectrum of 4-tert-butyl carbamate benzenesulfonamide prepared in Example 1;
[0035] Figure 2 The H-NMR spectrum of 4-tert-butyl carbamate ethanesulfonamide prepared in Example 2;
[0036] Figure 3 The H NMR spectrum of the lithium amide salt-1 prepared in Example 3;
[0037] Figure 4 The H-NMR spectrum of the lithium amide salt-2 prepared in Example 4;
[0038] Figure 5 The H NMR spectrum of the lithium amide salt-3 prepared in Example 5;
[0039] Figure 6 The H-NMR spectrum of the lithium amide salt-4 prepared in Example 6;
[0040] Figure 7 The H NMR spectrum of the lithium amide salt-5 prepared in Example 7;
[0041] Figure 8 The H-NMR spectrum of the lithium amide salt-6 prepared in Example 8;
[0042] Fig. 9 The H NMR spectrum of lithium amide salt-7 prepared in Example 9;
[0043] Fig.10 Infrared spectra of lithium amide salts-1 to lithium amide salts-7 prepared in Examples 3 to 9;
[0044] Fig.11 MTC-OPhF prepared in Example 10 5 H NMR spectrum;
[0045] Fig.12Example 10 Preparation of P(MTC-OPhF 5 )H NMR spectrum;
[0046] Fig.13 H-NMR spectrum of polymer electrolyte-1 prepared in Example 11;
[0047] Fig.14 X-ray photoelectron spectrum of polymer electrolyte-1 prepared in Example 11;
[0048] Fig.15 AC impedance diagram of the battery prepared in Example 13 at different temperatures;
[0049] Fig.16 Linear voltammetric scan of the battery prepared in Example 14;
[0050] Fig.17 Lithium ion migration number of the battery prepared in Example 15;
[0051] Fig.18 H-NMR spectrum of polymer electrolyte-2 prepared in Example 12. DETAILED DESCRIPTION
[0052] The following examples are intended to further illustrate the present invention. The following examples are only used to illustrate the present invention, but the present invention is not limited to these examples. All equivalent changes and modifications made within the scope of the present invention should fall within the scope of the present invention. The various raw materials involved in the specification were purchased from the market, and the sources and purity of some reagents and the models of the instruments used are shown in Tables 1 and 2.
[0053] Table 1 Source and purity of reagents
[0054]
[0055]
[0056] Table 2 Instruments and equipment
[0057] Instrument Name model factory Heating magnetic stirrer RCT Basic Germany IKA Group Electronic analytical balance BT-423S Sartorius Instruments Ltd. Nuclear Magnetic Resonance Spectrometer AVANCE500MHZNMR Bruker Fourier transform infrared spectrometer BRUKERVERTEX70 Bruker X-ray Photoelectron Spectrometer AXISSUPRA British Shimadzu Instruments Electrochemical workstation VMP300 Bio-Logic, France Button battery sealing machine BNP-FK26T-CK Shenzhen Bonap Company Glove box Universal(2440 / 750 / 900) Mikaelona Electromechanical Technology Co., Ltd.
[0058] Example 1
[0059] Mafenide hydrochloride (4170 mg, 20 mmol) and BOC 2 O (5110 μL, 22 mmol) was dissolved in tetrahydrofuran (100 mL), N,N-diisopropylethylamine (7000 μL, 40 mmol) was added, stirred at 500 r / min for 48 h, diluted with dichloromethane (1000 mL), washed with 1 mol / L HCl (500 mL), and then washed with saturated NaHCO 3(500 mL) washing. The organic phase was washed with anhydrous Na 2 SO 4 The residue was dried, filtered and concentrated to give white tert-butyl 4-carbamate benzenesulfonamide (5740 mg, 100% yield).
[0060] Example 2
[0061] 2-Aminoethanesulfonamide hydrochloride (3220 mg, 20 mmol) and BOC 2 O (5110 μL, 22 mmol) was dissolved in tetrahydrofuran (100 mL), N,N-diisopropylethylamine (7000 μL, 40 mmol) was added, stirred at 500 r / min for 48 h, diluted with dichloromethane (1000 mL), washed with 1 mol / L HCl (500 mL), and then washed with saturated NaHCO 3 (500mL) washing. The organic phase was added to anhydrous Na 2 SO 4 The organic layer was dried on the supernatant, filtered and concentrated to give white tert-butyl 4-carbamate ethanesulfonamide (3804 mg, 81% yield).
[0062] Example 3
[0063] Under argon atmosphere, 4-tert-butyl carbamate benzenesulfonamide (574 mg, 2 mmol) and DMAP (244 mg, 2 mmol) prepared in Example 1 and triethylamine (607 mg, 6 mmol) were dissolved in acetonitrile (4 mL) and cooled to 0°C by ice bath. Benzenesulfonyl chloride (353 mg, 2 mmol) was dissolved in 4 mL of acetonitrile and cooled to 0°C by ice bath. The solution was slowly added dropwise to the above solution and reacted in an ice bath for 0.5 h, then at room temperature for 48 h, concentrated by rotary evaporation, and dissolved in 20 mL of dichloromethane (DCM). 4 wt% NaHCO 3 The product was washed once with 10 mL of 1 mol / L HCl solution; washed twice with 10 mL of 1 mol / L HCl solution, the solvent was removed by rotary evaporation, dissolved in tetrahydrofuran (4 mL), added with 2 mol / L HCl solution (4 mL), stirred at room temperature at 500 r / min for 48 h, filtered and dried to obtain aminosulfonyl imide hydrochloride (578 mg, 1.60 mmol), and then neutralized with 2 equal parts of lithium hydroxide (3.20 mmol) in water (2 mL), and dried to obtain amino lithium salt-1 (Li-1).
[0064] Example 4
[0065] Under argon atmosphere, 4-tert-butyl 4-carbamate ethanesulfonamide (448 mg, 2 mmol), DMAP (244 mg, 2 mmol) and triethylamine (607 mg, 6 mmol) prepared in Example 2 were dissolved in acetonitrile (4 mL) and cooled to 0°C with an ice bath. Benzenesulfonyl chloride (353 mg, 2 mmol) was dissolved in acetonitrile (4 mL) and cooled to 0°C with an ice bath. The solution was slowly added dropwise to the solution and reacted in an ice bath for 0.5 h, then at room temperature for 48 h, concentrated by rotary evaporation, and dissolved in 20 mL of DCM. 4 wt% NaHCO 3 The product was washed once with 10 mL of 1 mol / L HCl solution; washed twice with 10 mL of 1 mol / L HCl solution, the solvent was removed by rotary evaporation, dissolved in tetrahydrofuran (4 mL), added with 2 mol / L HCl solution (4 mL), stirred at room temperature and 500 r / min for 48 h, filtered and dried to obtain aminosulfonyl imide hydrochloride (440 mg, 1.46 mmol), and then neutralized with 2 equal parts of lithium hydroxide (2.92 mmol) in water (2 mL), and dried to obtain amino lithium salt-2 (Li-2).
[0066] Example 5
[0067] Under argon atmosphere, 4-tert-butyl carbamate benzenesulfonamide (574 mg, 2 mmol), DMAP (244 mg, 2 mmol) and triethylamine (607 mg, 6 mmol) prepared in Example 1 were dissolved in acetonitrile (4 mL) and cooled to 0°C with an ice bath. Trifluoromethanesulfonyl chloride (337 mg, 2 mmol) was dissolved in 4 mL of acetonitrile and cooled to 0°C with an ice bath. The solution was slowly added dropwise to the above solution and reacted in an ice bath for 0.5 h, then at room temperature for 48 h, concentrated by rotary evaporation, and dissolved in 20 mL of DCM. 4 wt% NaHCO 3 The product was washed once with 10 mL of 1 mol / L HCl solution; washed twice with 10 mL of 1 mol / L HCl solution, the solvent was removed by rotary evaporation, dissolved in tetrahydrofuran (4 mL), added with 2 mol / L HCl solution (4 mL), stirred at room temperature and 500 r / min for 48 h, filtered and dried to obtain aminosulfonyl imide hydrochloride (480 mg, 1.36 mmol), and then 2 equal parts of lithium hydroxide (2.72 mmol) were added to water (2 mL) for neutralization. After drying, amino lithium salt-3 (Li-3) was obtained.
[0068] Example 6
[0069] Under argon atmosphere, 4-tert-butyl carbamate ethanesulfonamide (448 mg, 2 mmol), DMAP (244 mg, 2 mmol) and triethylamine (607 mg, 6 mmol) prepared in Example 2 were dissolved in acetonitrile (4 mL) and cooled to 0°C with an ice bath. 4-Fluorobenzenesulfonyl chloride (389 mg, 2 mmol) was dissolved in 4 mL of acetonitrile and cooled to 0°C with an ice bath. The mixture was slowly added dropwise to the above solution and reacted in an ice bath for 0.5 h, then at room temperature for 48 h, concentrated by rotary evaporation, and dissolved in 20 mL of DCM. 4 wt% NaHCO 3 The product was washed once with 10 mL of 1 mol / L HCl solution; washed twice with 10 mL of 1 mol / L HCl solution, the solvent was removed by rotary evaporation, dissolved in tetrahydrofuran (4 mL), added with 2 mol / L HCl solution (4 mL), stirred at room temperature and 500 r / min for 48 h, filtered and dried to obtain aminosulfonyl imide hydrochloride (508 mg, 1.60 mmol), and then neutralized with 2 equal parts of lithium hydroxide (3.20 mmol) in water (2 mL), and dried to obtain amino lithium salt-4 (Li-4).
[0070] Example 7
[0071] Under argon atmosphere, 4-tert-butyl carbamate benzenesulfonamide (574 mg, 2 mmol), DMAP (244 mg, 2 mmol) and triethylamine (607 mg, 6 mmol) prepared in Example 1 were dissolved in acetonitrile (4 mL) and cooled to 0°C with an ice bath; 4-fluorobenzenesulfonyl chloride (389 mg, 2 mmol) was dissolved in 4 mL of acetonitrile, cooled to 0°C with an ice bath, and slowly added dropwise to the above solution, reacted in an ice bath for 0.5 h, then reacted at room temperature for 48 h, concentrated by rotary evaporation, and dissolved in 20 mL of DCM; 4 wt% NaHCO 3 The product was washed once with 10 mL of 1 mol / L HCl solution; washed twice with 10 mL of 1 mol / L HCl solution, the solvent was removed by rotary evaporation, dissolved in tetrahydrofuran (4 mL), added with 2 mol / L HCl solution (4 mL), stirred at room temperature and 500 r / min for 48 h, filtered and dried to obtain aminosulfonyl imide hydrochloride (456 mg, 1.20 mmol), and then neutralized with 2 equal parts of lithium hydroxide (2.40 mmol) in water (2 mL), and dried to obtain amino lithium salt-5 (Li-5).
[0072] Example 8
[0073] Under argon atmosphere, 4-tert-butyl carbamate benzenesulfonamide (574 mg, 2 mmol), DMAP (244 mg, 2 mmol) and triethylamine (607 mg, 6 mmol) prepared in Example 1 were dissolved in acetonitrile (4 mL) and cooled to 0°C with an ice bath; 4-trifluoromethoxybenzenesulfonyl chloride (521 mg, 2 mmol) was dissolved in 4 mL of acetonitrile, cooled to 0°C with an ice bath, and slowly added dropwise to the above solution. The mixture was reacted in an ice bath for 0.5 h, and then reacted at room temperature for 48 h. The mixture was concentrated by rotary evaporation and dissolved in 20 mL of DCM; 4 wt% NaHCO 3 The product was washed once with 10 mL of 1 mol / L HCl solution; washed twice with 10 mL of 1 mol / L HCl solution, the solvent was removed by rotary evaporation, dissolved in tetrahydrofuran (4 mL), added with 2 mol / L HCl solution (4 mL), stirred at room temperature and 500 r / min for 48 h, filtered and dried to obtain aminosulfonyl imide hydrochloride (625 mg, 1.40 mmol), and then neutralized with 2 equal parts of lithium hydroxide (2.80 mmol) in water (2 mL), and dried to obtain amino lithium salt-6 (Li-6).
[0074] Example 9
[0075] Under argon atmosphere, 4-tert-butyl carbamate benzenesulfonamide (574 mg, 2 mmol), DMAP (244 mg, 2 mmol) and triethylamine (607 mg, 6 mmol) prepared in Example 1 were dissolved in acetonitrile (4 mL) and cooled to 0°C with an ice bath; 4-trifluoromethylbenzenesulfonyl chloride (489 mg, 2 mmol) was dissolved in 4 mL of acetonitrile, cooled to 0°C with an ice bath, and slowly added dropwise to the above solution. The reaction was carried out in an ice bath for 0.5 h, and then at room temperature for 48 h. The mixture was concentrated by rotary evaporation and dissolved in 20 mL of DCM; 4 wt% NaHCO 3 The product was washed once with 10 mL of 1 mol / L HCl solution; washed twice with 10 mL of 1 mol / L HCl solution, the solvent was removed by rotary evaporation, dissolved in tetrahydrofuran (4 mL), added with 2 mol / L HCl solution (4 mL), stirred at room temperature and 500 r / min for 48 h, filtered and dried to obtain aminosulfonyl imide hydrochloride (559 mg, 1.30 mmol), and then neutralized with 2 equal parts of lithium hydroxide (2.60 mmol) in water (2 mL), and dried to obtain amino lithium salt-7 (Li-7).
[0076] Example 10
[0077] Reference Engler AC, Chan JMW, Coady DJ et al.; Accessing New Materialsthrough Polymerization and Modification of a Polycarbonate with a PendantActivated Ester. Macromolecules. 2013, 46, 1283-1290. Preparation of P(MTC-OPhF 5 ).
[0078] (1) Dissolve 2,2-di(hydroxymethyl)propionic acid (3.00 g, 22 mmol), bis(pentafluorophenyl) carbonate (21.70 g, 55 mmol) and cesium fluoride (0.7 g, 4.6 mmol) in 70 mL of anhydrous tetrahydrofuran (THF) and stir at 500 r / min for 20 h. Remove the solvent by rotary evaporation, and dissolve the residue in dichloromethane (100 mL), filter, and wash the filtrate with saturated NaHCO 3 (100 mL) and washed with MgSO 4 The solvent was removed by rotary evaporation, and the product was recrystallized from ethyl acetate / hexane (2:1) to obtain white crystalline powder MTC-OPhF 5 (4303 mg, 13.2 mmol);
[0079] (2) Under argon atmosphere, take the MTC-OPhF prepared in step (1) 5 (326 mg, 1.00 mmol) and PEG400 (4 mg, 0.01 mmol) were dissolved in dichloromethane (1 mL). MTC-OPhF5 was only partially dissolved at this concentration, and then trifluoromethanesulfonic acid (8 mg, 0.05 mmol) was added. As the stirring reaction proceeded, the undissolved MTC-OPhF5 slowly entered the solution. The reaction was stirred at room temperature at 500 r / min for 16 h. The resulting mixture was precipitated into n-hexane twice and dried in vacuo to obtain P(MTC-OPhF 5 )(265mg, 0.81mmol).
[0080] Embodiment 11
[0081] Take P(MTC-OPhF prepared in Example 10 5)(326 mg, structural unit number 1 mmol) and the amino lithium salt-1 (332 mg, 1 mmol) prepared in Example 3 were dissolved in N, N-dimethylformamide (2 mL), reacted at room temperature for 3 h, and then transferred to a dialysis bag with a molecular weight cutoff of 1000, dialyzed in pure water, and freeze-dried to remove the solvent to obtain polymer electrolyte-1 (SPE-1). Polymer electrolyte-1 (30 mg) and polyethylene oxide 60w (70 mg) were dissolved in acetonitrile (3 mL), and the resulting mixed solution was poured into a polytetrafluoroethylene mold, evaporated at room temperature for 12 h, and then transferred to a vacuum oven at 60°C for vacuum drying for 12 h to obtain a composite polymer electrolyte.
[0082] Example 12
[0083] The amino lithium salt-1 (332 mg, 1 mmol) prepared in Example 3 and glutaraldehyde (50 mg, 0.5 mmol) were dissolved in N,N-dimethylformamide (1 mL), reacted at room temperature for 30 min, and then polyethylene glycol dicarboxylic acid (593 mg, 0.5 mmol) and tert-butyl isocyanate (84 mg, 1 mmol) were added, and reacted at 50 ° C for 24 h. The reaction solution was precipitated into ether twice and dried to obtain polymer electrolyte-2 (SPE-2).
[0084] Example 13
[0085] In a glove box, the composite polymer electrolyte prepared in Example 11 was dissolved in methanol and cast on a polytetrafluoroethylene mold. After drying, it was cut into discs with a diameter of 16 mm. In the order of "negative electrode shell-steel sheet-electrolyte membrane-steel sheet-gasket-spring-positive electrode shell", a CR 2032 button cell was assembled. The ionic conductivity of the electrolyte was tested by AC impedance using an electrochemical workstation.
[0086] Embodiment 14
[0087] In a glove box, the composite polymer electrolyte prepared in Example 11 was dissolved in methanol and cast on a polytetrafluoroethylene mold. After drying, it was cut into discs with a diameter of 16 mm. In the order of "negative electrode shell-lithium sheet-electrolyte membrane-steel sheet-gasket-spring-positive electrode shell", a CR 2032 button cell was assembled. The ionic conductivity of the electrolyte was tested using an electrochemical workstation with linear voltammetric scanning.
[0088] Embodiment 15
[0089] In a glove box, the composite polymer electrolyte prepared in Example 11 was dissolved in methanol and cast on a polytetrafluoroethylene mold. After drying, it was cut into discs with a diameter of 16 mm. In the order of "negative electrode shell-lithium sheet-electrolyte membrane-lithium sheet-gasket-spring-positive electrode shell", a CR 2032 button cell was assembled. The lithium ion mobility of the electrolyte was tested by chronoamperometry using an electrochemical workstation.
[0090] The amide lithium salts-1 to amide lithium salts-7 prepared in Examples 3 to 9 were characterized by H NMR spectra and IR tests. The results are as follows: Figure 3-Figure 10 , confirming the synthesis of various amino lithium salts with different molecular structures.
[0091] The polymer electrolyte-1 prepared in Example 11 was characterized by nuclear magnetic hydrogen spectrum and X-ray photoelectron spectroscopy. The results are as follows: Fig.13 and Fig.14 , confirming that the amino lithium salt was successfully grafted onto the polymer main chain to obtain polymer electrolyte-1.
[0092] The composite polymer electrolyte prepared in Example 11 was tested for ionic conductivity by AC impedance, ionic conductivity by linear voltammetry, and lithium ion mobility by chronoamperometry. The results are as follows: Figure 15-17 , confirming that the composite polymer electrolyte has a certain ionic conductivity (the thickness of the electrolyte membrane is 51.2 μm, and the calculated value is 1.84×10 -6 S cm -1 , 1.23×10 at 70℃ -6 S cm -1 ) and the electrochemical window reaches 5.2V, the lithium ion migration number is 0.73, and its ionic conductivity can meet the battery charging and discharging requirements at high temperatures. It can also stably exist in the battery system with high-voltage positive electrode to improve the energy density of the battery. The lithium ion migration number is much higher than that of ordinary polymer electrolytes, which can effectively reduce the polarization inside the battery.
[0093] The polymer electrolyte-2 prepared in Example 12 was characterized by H NMR spectroscopy. The results are as follows: Fig.18 , confirming that amino lithium salt successfully reacted with other monomers to obtain polymer electrolyte-2 (SPE-2).
[0094] In summary, the present invention proposes an amino lithium salt with a higher activity end group, so it is suitable for more chemical reactions, fixes the lithium salt fragment on the polymer chain, and the anion does not move, so as to obtain a single ion conductor polymer solid electrolyte with a higher lithium ion migration number. The single ion conductor polymer solid electrolyte prepared by the present invention has excellent electrochemical properties, ionic conductivity and a lithium ion migration number of up to 0.73, which can meet the battery use and can match the high-voltage positive electrode to improve the energy density of the battery, so it has good commercial promotion potential.
[0095] According to the above description, those skilled in the art can also change and modify the above implementation. Therefore, the present invention is not limited to the above specific implementation, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention.
Claims
1. An amide lithium salt, characterized in that: The structural formula of the lithium amide salt is shown in formula (I), In the formula, R1 and R2 are each independently selected from one of a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, a substituted or unsubstituted alkynyl group and a substituted or unsubstituted heteroatom-containing group; wherein, when substituted, the substituent is selected from halogen; the heteroatom includes at least one of B, N, O, Si, P, and S, the number of carbon atoms in the alkyl group is less than or equal to 10, the number of carbon atoms in the alkenyl group is less than or equal to 10, and the number of carbon atoms in the alkynyl group is less than or equal to 10.
2. The lithium amide salt according to claim 1, characterized in that: Prepared by the reaction of sulfonamide hydrochloride and sulfonyl chloride, the structural formula of the sulfonamide hydrochloride is shown in formula (II), and the structural formula of the sulfonyl chloride is shown in formula (III); The molar ratio of the sulfonamide hydrochloride to the sulfonyl chloride is 1:
1.
3. A method for preparing the lithium amide salt according to claim 2, characterized in that: The following steps are involved: (1) Amino group protection of amino hydrochloride: sulfonamide hydrochloride and di-tert-butyl dicarbonate are reacted in an alkaline solvent with stirring, and the resulting reaction solution is diluted with dichloromethane, and then washed with 1 mol / L HCl aqueous solution and saturated NaHCO3 in sequence. The organic phase is dried and concentrated by rotary evaporation to obtain an N-tert-butyloxycarbonylamino compound; (2) Synthesis of lithium amide salt precursor: Under argon environment, the N-tert-butyloxycarbonylamino compound prepared in step (1) is reacted with sulfonyl chloride in a molar ratio of 1: (1 to 1.5) in an organic solvent, the obtained reaction solution is concentrated by rotary evaporation, dichloromethane is added to dissolve, and then washed with NaHCO3 solution and HCl in sequence. After the organic phase is dried, the solvent is removed by rotary evaporation to obtain N-tert-butyloxycarbonylsulfonyl imide; (3) Removal of the protecting group of lithium amide salt: the N-tert-butyloxycarbonylsulfonyl imide prepared in step (2) is reacted in trifluoroacetic acid or an acid solution of HCl aqueous solution / organic solvent, and stirred. The obtained reaction solution is then evaporated to remove the solvent to obtain aminosulfonyl imide hydrochloride; (4) Neutralization reaction of amide lithium salt: The aminosulfonyl imide hydrochloride prepared in step (3) and lithium hydroxide are neutralized in a solvent to obtain amide lithium salt.
4. The method for preparing an amide lithium salt according to claim 3, characterized in that: Step (1) is: dissolving sulfonamide hydrochloride and di-tert-butyl dicarbonate in tetrahydrofuran, adding 2 equal parts of sulfonamide hydrochloride in N,N-diisopropylethylamine or triethylamine, stirring and reacting for 48 hours, diluting the obtained reaction solution with dichloromethane, and then washing with 1 mol / L HCl aqueous solution and saturated NaHCO3 in sequence, drying the organic phase and concentrating by rotary evaporation to obtain an N-tert-butyloxycarbonylamino compound; the molar ratio of the sulfonamide hydrochloride to di-tert-butyl dicarbonate is 1: (1 to 1.5).
5. The method for preparing an amide lithium salt according to claim 3, characterized in that: Step (2) comprises: under an argon environment, dissolving the N-tert-butoxycarbonylamino compound prepared in step (1) in acetonitrile with 4-dimethylaminopyridine and triethylamine to obtain a solution of N-tert-butoxycarbonylamino compound; dissolving sulfonyl chloride in acetonitrile to obtain a sulfonyl chloride solution; adding the sulfonyl chloride solution to the solution of N-tert-butoxycarbonylamino compound; reacting at 0°C for 30 minutes; and then stirring at room temperature for 48 hours; concentrating the obtained reaction solution by rotary evaporation; adding dichloromethane to dissolve the reaction solution; and then washing with 3wt% to 5wt% NaHCO3 and 1mol / L HCl in sequence; and drying the organic phase and removing the solvent by rotary evaporation to obtain N-tert-butoxycarbonylsulfonyl imide; The molar ratio of the N-tert-butoxycarbonylamino compound, 4-dimethylaminopyridine, triethylamine and sulfonyl chloride is 1:1:3:(1-1.5); the concentration of the N-tert-butoxycarbonylamino compound in the N-tert-butoxycarbonylamino compound solution is 0.5 mol / L, and the concentration of the sulfonyl chloride solution is 0.5 mol / L.
6. The method for preparing an amide lithium salt according to claim 3, characterized in that: Step (3) comprises: reacting the N-tert-butoxycarbonylsulfonyl imide prepared in step (2) in trifluoroacetic acid or 1-2 mol / L HCl aqueous solution / tetrahydrofuran acid solution with stirring for 48 hours, and removing the solvent from the obtained reaction solution by rotary evaporation to obtain aminosulfonyl imide hydrochloride, wherein the volume ratio of HCl to tetrahydrofuran is 1:1, the molar ratio of the N-tert-butoxycarbonylsulfonyl imide to trifluoroacetic acid is 1:2, and the molar ratio of the N-tert-butoxycarbonylsulfonyl imide to HCl in the acid solution is 1:
2.
7. The method for preparing an amide lithium salt according to claim 3, characterized in that: In step (4), the molar ratio of aminosulfonyl imide hydrochloride to lithium hydroxide is 1:2, and the solvent is selected from any one of water, N,N-dimethylformamide, and dimethyl sulfoxide.
8. A polymer electrolyte, characterized in that: It is prepared by reacting the amino lithium salt according to claim 1 with a polymer matrix, wherein the polymer matrix has a structural formula as shown in formula (IV), In the formula, R3 is selected from hydrogen, halogen, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted heteroatom-containing group. When substituted, the substituent is selected from halogen; the heteroatom includes at least one of B, N, O, Si, P, and S; the number of carbon atoms in the alkyl group is less than or equal to 10, the number of carbon atoms in the alkenyl group is less than or equal to 10, and the number of carbon atoms in the alkynyl group is less than or equal to 10; The preparation method is as follows: reacting the structural units of the amino lithium salt and the polymer matrix in an alkaline solvent at a molar ratio of 1:1 for 3 hours with stirring, and removing the solvent after rotary evaporation or dialyzing the obtained reaction solution in pure water to obtain a polymer electrolyte with a structural formula as shown in formula (V). The alkaline solvent is N,N-dimethylformamide or dimethyl sulfoxide containing 1% triethylamine.
9. A polymer electrolyte, characterized in that The preparation method comprises: reacting the lithium amide salt described in claim 1 with a dibasic acid, a dialdehyde and an isonitrile in a molar ratio of 1:0.5:0.5:1 to obtain a polymer electrolyte having a structural formula as shown in formula (VI). In the formula, R4-R6 are selected from substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aromatic group, substituted or unsubstituted heteroatom-containing group, wherein, When substituted, the substituent is selected from halogen; the heteroatom includes at least one of B, N, O, Si, P, and S, the number of carbon atoms in the alkyl group is less than or equal to 10, the number of carbon atoms in the alkenyl group is less than or equal to 10, and the number of carbon atoms in the alkynyl group is less than or equal to 10.
10. The polymer electrolyte according to claim 8 or 9, characterized in that: Other components are also included, and the other components are selected from lithium perchlorate, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium difluorophosphate, lithium difluorobisoxalate phosphate, lithium tetrafluorooxalate phosphate, lithium oxalate phosphate, lithium bisoxalate borate, lithium difluorooxalate borate, lithium tetrafluoroborate, bisdifluorosulfonyl imide lithium salt, bistrifluoromethylsulfonyl imide lithium, ether, benzene, toluene, xylene, chloroform, carbon disulfide, acetonitrile, acetone, N,N-dimethylpyrrolidone, N,N-dimethylformamide, ethylene carbonate, propylene carbonate, butylene carbonate, ethylene sulfite, propylene sulfite, dimethyl sulfite, diethyl sulfite, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethylene carbonate, allyl methyl carbonate Ester, vinyl ethylene carbonate, fluoroethylene carbonate, ethyl propionate, propyl propionate, ethyl acetate, ethyl butyrate, γ-butyrolactone, ethylene glycol dimethyl ether, tetrahydrofuran, tetrahydropyran, dioxolane, dimethyl sulfoxide, dimethyl sulfone, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylic acid, polyacrylonitrile, polymethyl methacrylate carbonate, polyethylene oxide, polyethylene, polypropylene, polyamide, polyimide, polyvinyl alcohol, polyvinyl butyral, polysiloxane, polytetrafluoroethylene, polytrimethylene carbonate, inorganic filler oxide solid electrolyte, sulfide solid electrolyte, silicon oxide, silicon dioxide, titanium oxide, zirconium oxide, aluminum oxide, boehmite, montmorillonite, succinonitrile or one or more thereof.
Citation Information
Cited By
Difunctional aqueous zinc ion battery high-voltage electrolyte and preparation method and application thereof
CN121149453A